ChemInform Abstract: Discovery of Spin Glass Behavior in Ln2Fe4Sb5 (Ln: La—Nd and Sm). Issue 6 (20th February 2013) - Phelan, W. Adam; Nguyen, Giang V.; Wang, Jiakui K.; McCandless, Gregory T.; Morosan, Emilia; DiTusa, John F.; Chan, Julia Y.
Abstract Single crystals of the title compounds are prepared from the elements using an inert Bi flux.